The Mediating Role of Electronic Word of Mouth in The Effect of Social Media Marketing on Purchase Intention (A Study At Good Karma Warung Tirtagangga, Karangasem Regency) - Patma Ari Ayu Kartini; I Gusti Ngurah Jaya Agung Widagda (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Social media marketing is a promotional strategy that leverages social media platforms to advertise products, services, or brands by actively engaging with audiences. This approach is effective in capturing consumer attention, encouraging their participation, and plays a critical role in shaping purchase intention through broad reach and direct interaction. This study aims to examine and explain the influence of social media marketing on purchase intention with electronic word of mouth (e-WOM) as a mediating variable, focusing on Good Karma Warung Tirtagangga. The sample consisted of 120 respondents selected using purposive sampling. Data were collected through interviews and online questionnaires. The analytical techniques employed in this study include path analysis, the Sobel test, and the Variance Accounted For (VAF) test, using SPSS version 27. The results reveal that social media marketing has a positive and significant effect on purchase intention, social media marketing positively and significantly affects electronic word of mouth, electronic word of mouth has a positive and significant impact on purchase intention, and electronic word of mouth successfully mediates the relationship between social media marketing and purchase intention.